N-acetylcysteine for the prevention of stricture after circumferential endoscopic submucosal dissection of the esophagus: a randomized trial in a porcine model - Barret, Maximilien (BioMed Central, 2012)
BACKGROUND: Circumferential endoscopic submucosal dissection (CESD) of the esophagus would allow for both the eradication of Barrett’s esophagus and its related complications, such as advanced neoplasia. However, such procedures generally induce inflammatory repair resulting in a fibrotic stricture. N-acetylcysteine (NAC) is an antioxidant that has shown some efficacy against pulmonary and hepatic fibrosis. The aim of our study was to evaluate the benefit of NAC in the prevention of esophageal cicatricial stricture after CESD in a swine model. ANIMALS AND METHODS: Two groups of six pigs each were subjected to general anesthesia and CESD: after randomization, a first group received an oral NAC treatment regimen of 100 mg/kg/day, initiated one week before the procedure, whereas a second group was followed without any prophylactic treatment. Follow-up endoscopies took place seven, fourteen, twenty-one, and twenty-eight days after CESD. Necropsy, histological assessment of esophageal inflammation, and fibrosis were performed on day 28. RESULTS: The median esophageal lumen diameter on day 21 (main judgment criterion) was 4 mm (range 2 to 5) in group 1 and 3 mm (range 1 to 7) in group 2 (P = 0.95). No significant difference was observed between the two groups regarding clinical evaluation (time before onset of clinically significant esophageal obstruction), number of dilations, esophageal inflammation and fibrosis, or oxidative stress damage on immunohistochemistry. CONCLUSIONS: Despite its antioxidant effect, systemic administration of NAC did not show significant benefit on esophageal fibrosis in our animal model of esophageal wound healing within the experimental conditions of this study. Since the administered doses were relatively high, it seems unlikely that NAC might be a valuable option for the prevention of post-endoscopic esophageal stricture.